The excitement of discovery : selected papers of Alexander Rich : a tribute to Alexander Rich - Zhang, Shuguang (Series in structural biology, 2019)
This book is intended for students and general readers interested in the structures of biological molecules and the history of science. It highlights Alexander Rich's pioneering contributions to nucleic acid research, including work on RNA and DNA structures, information transfer from RNA to protein, and ribosome function, while also covering studies on proteins and viruses. The book traces key discoveries achieved through X-ray diffraction techniques, from fiber scattering to high-resolution crystal structures, showcasing milestones such as the first detailed structures of RNA base pairing and the identification of a novel DNA conformation. Overall, it offers a rich historical perspective on the early development of modern molecular biology and Rich's central role in advancing structural studies of biological macromolecules.